Structural health monitoring using distributed fiber optic sensors - Ong, Wan Teng. (2010)
This project aims to design a real time structural health monitoring (SHM) system for the monitoring of underground caverns. This research will focus on the strain and displacement experienced by the specimens under different cases of loadings. The specimens will be linked and monitored by optic fibers, Brillouin optical time-domain Reflectometer (BOTDR), strain gauges and linear variable displacement transducers (LVDT). The first experiment was tested with a steel I-beam to determine the reliability of the red optic fiber cable. The results obtained from experimental, numerical and theoretical were then compared and discussed. The second experiment was tested with a steel frame structure with two different setups of the red optic fiber cable. The results obtained from the two setups were being correlated with a 3-dimensional model in Ansys Workbench. The author will then conclude the better setup that is more suitable for installation of the red optic fiber cable practically in the underground caverns.